Contingent assessment of the COVID-19 vaccine (2020)
The COVID-19 pandemic has not only had a negative impact on people’s health and life behavior, but also on economies around the world. At the same time, laboratories and institutions are working hard to obtain a COVID-19 vaccine, which we hope will be available soon. However, there has been no assessment of whether an individual and society value a vaccine monetarily, and what factors determine this value. Therefore, the objective of this research was to estimate the individual’s willingness to pay (WTP) for a hypothetical COVID-19 vaccine and, at the same time, find the main factors that determine this valuation. For this, we used the contingent valuation approach, in its single and double-bounded dichotomous choice format, which was based on a hypothetical market for a vaccine. The sample used was obtained through an online survey of n = 566 individuals from Chile. The main results showed that the WTP depends on the preexistence of chronic disease (p 0:05), knowledge of COVID-19 (p 0:05), being sick with COVID-19 (p 0:05), perception of government performance (p 0:01), employment status (p 0:01), income (p 0:01), health care (p 0:05), adaptation to quarantine with children at home (p 0:01Þ and whether the person has recovered from COVID-19 (p 0:10Þ. According to our discrete choice model in double-bounded dichotomous format, it was concluded that the individuals’ WTP is US$184.72 (CI: 165.52–203.92; p < 0.01). This implies a social valuation of approximately US$2232 million, corresponding to 1.09% of the GNP per capita.